2000
DOI: 10.1046/j.1365-2184.2000.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative model for differential motility of gliomas in grey and white matter

Abstract: We have extended a mathematical model of gliomas based on proliferation and diffusion rates to incorporate the effects of augmented cell motility in white matter as compared to grey matter. Using a detailed mapping of the white and grey matter in the brain developed for a MRI simulator, we have been able to simulate model tumours on an anatomically accurate brain domain. Our simulations show good agreement with clinically observed tumour geometries and suggest paths of submicroscopic tumour invasion not detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
476
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 402 publications
(491 citation statements)
references
References 14 publications
10
476
0
5
Order By: Relevance
“…Previous studies of the motility of gliomas have demonstrated that diffusion is an accurate estimation for the spread of gliomas (Woodward et al, 1996;Swanson, 1999). A consequence of modeling cellular motility by Fickian or gradient-driven diffusion, is the lack of a definitive interface between malignant and normal tissue.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies of the motility of gliomas have demonstrated that diffusion is an accurate estimation for the spread of gliomas (Woodward et al, 1996;Swanson, 1999). A consequence of modeling cellular motility by Fickian or gradient-driven diffusion, is the lack of a definitive interface between malignant and normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Previous two-dimensional models have suggested that tumour location can have a significant impact on survival time based simply on the local invasion abilities of the tumour (Swanson, 1999;Swanson et al, 2000). Figure 3 shows the survival times (time between diagnosis at 3 cm diameter and death at 6 cm diameter) predicted by the model for a range of values of the ratio of the tumour cell migration rate in white matter to that in grey matter (g= D w /D g ).…”
Section: Virtual Gliomasmentioning
confidence: 98%
See 3 more Smart Citations